(untitled) (Journal of history, 2020)
Problems and perspectives for the development of energy relations between Kazakhstan and Russia are becoming relevant in the context of reforming the Kazakhstani economy and globalization of the world economy, which dictate the growing interdependence and interaction of national economies. The character of the emerging new system of global and regional world order is especially pronounced in the Eurasian region, which has become important and dynamic from a geopolitical and economic point of view. The geopolitical situation around this region is characterized by a combination and clash of national interests of the main centers of the world economy and policy, such as USA, EU, Russia and China. The purpose of the article is to analyze the bilateral relations of the EAEU member countries – Russia and Kazakhstan in the energy sector in the new geopolitical conditions. In accordance with the goal, the following tasks were set: to reveal the specific features and imperatives of energy cooperation between countries; identify the reasons for the interest of Russia and Kazakhstan in the integration interaction in the field of energy policy, identify priority areas for the development of energy interaction.